Everyday executive functions in Down syndrome from early childhood to young adulthood: evidence for both unique and shared characteristics compared to youth with sex chromosome trisomy (XXX and XXY) - Lee, Nancy Raitano; Anand, Payal; Will, Elizabeth; Adeyemi, Elizabeth I.; Clasen, Liv S.; Blumenthal, Jonathan D.; Giedd, Jay N.; Daunhauer, Lisa A.; Fidler, Deborah J.; Edgin, Jamie O. (Frontiers in Behavioral Neuroscience, 2015)
Executive functions (EF) are thought to be impaired in Down syndrome (DS) and sex chromosome trisomy (Klinefelter and Trisomy X syndromes; +1X). However, the syndromic specificity and developmental trajectories associated with EF difficulties in these groups are poorly understood. The current investigation (a) compared everyday EF difficulties in youth with DS, +1X, and typical development (TD); and (b) examined relations between age and EF difficulties in these two groups and a TD control group cross-sectionally. Study 1 investigated the syndromic specificity of EF profiles on the Behavior Rating Inventory of Executive Function (BRIEF) in DS (n=30), +1X (n=30), and a TD group (n=30), ages 5-18 years. Study 2 examined age effects on EF in the same cross-sectional sample of participants included in Study 1. Study 3 sought to replicate Study 2’s findings for DS by examining age-EF relations in a large independent sample of youth with DS (n=85) and TD (n=43), ages 4-24 years. Study 1 found evidence for both unique and shared EF impairments for the DS and +1X groups. Most notably, youth with +1X had relatively uniform EF impairments on the BRIEF scales, while the DS group showed an uneven BRIEF profile with relative strengths and weaknesses. Studies 2 and 3 provided support for fairly similar age-EF relations in the DS and TD groups. In contrast, for the +1X group, findings were mixed; 6 BRIEF scales showed similar age-EF relations to the TD group and 2 showed greater EF difficulties at older ages for +1X. These findings will be discussed within the context of efforts to identify syndrome specific cognitive-behavioral profiles for youth with different genetic syndromes in order to inform basic science investigations into the etiology of EF difficulties in these groups and to develop treatment approaches that are tailored to the needs of these groups.